Pengaruh Pemberian Pupuk Dolomit dan SP-36 Terhadap Pertumbuhan dan Perkembangan Tanaman Cabai Merah (Capsicum annum L.) - Aulia, Tia; Harahap, Rahmaniah; Miyarnis, Miyarnis (UNIVERSITAS LABUHANBATU, 2025)
This study aims to determine the effect of dolomite and SP-36 fertilizer on the growth and production of red chili plants (Capsicum annum L.). The hypothesis tested in this study is the existence of a single response to dolomite and SP-36, as well as the interaction of both on the growth and production of red chili. The study was conducted from May to July 2024 at the experimental garden of the Faculty of Agriculture, Indonesian Community Development University (UPMI) Medan, using a factorial Randomized Block Design (RAK) with two factors: (1) Dolomite with three levels (D0 = without dolomite, D1 = 5 g/plot, D2 = 10 g/plot) and (2) SP-36 with three levels (S0 = without SP-36, S1 = 4.03 g/plot, S2 = 6.03 g/plot), with 9 treatment combinations. The results showed that dolomite administration had a very significant effect on the number of branches, fruit weight of sample plants, and fruit weight per plot, but was not significant on plant height and number of leaves at all observation ages. The treatment of dolomite 10 g/plot (D2) gave the best results for most parameters compared to the control (D0) and a dose of 5 g/plot (D1). The application of SP-36 fertilizer also had a very significant effect on the weight of the sample plant fruit and the weight of fruit per plot, but was not significant on plant height, number of leaves, and number of branches. The treatment of SP-36 at a dose of 6.03 g/plot (S2) showed the best results on several growth and production parameters. The interaction between dolomite and SP-36 had a very significant effect on the number of branches and weight of fruit per plot, but was not significant on other vegetative parameters. This study shows that the application of dolomite and SP-36 fertilizers significantly increases the production of red chili plants, especially in terms of the number of branches and fruit weight, with optimal doses of dolomite 10 g/plot and SP-36 6.03 g/plot. Keywords: dolomite fertilizer, SP-36, red chili